A controlled, before-and-after trial of an urban sanitation intervention to reduce enteric infections in children: research protocol for the Maputo Sanitation (MapSan) study, Mozambique. Issue 6 (18th June 2015) - Brown, Joe; Cumming, Oliver; Bartram, Jamie; Cairncross, Sandy; Ensink, Jeroen; Holcomb, David; Knee, Jackie; Kolsky, Peter; Liang, Kaida; Liang, Song; Nala, Rassul; Norman, Guy; et al.
Abstract : Introduction: Access to safe sanitation in low-income, informal settlements of Sub-Saharan Africa has not significantly improved since 1990. The combination of a high faecal-related disease burden and inadequate infrastructure suggests that investment in expanding sanitation access in densely populated urban slums can yield important public health gains. No rigorous, controlled intervention studies have evaluated the health effects of decentralised (non-sewerage) sanitation in an informal urban setting, despite the role that such technologies will likely play in scaling up access. Methods and analysis: We have designed a controlled, before-and-after (CBA) trial to estimate the health impacts of an urban sanitation intervention in informal neighbourhoods of Maputo, Mozambique, including an assessment of whether exposures and health outcomes vary by localised population density. The intervention consists of private pour-flush latrines (to septic tank) shared by multiple households in compounds or household clusters. We will measure objective health outcomes in approximately 760 children (380 children with household access to interventions, 380 matched controls using existing shared private latrines in poor sanitary conditions), at 2 time points: immediately before the intervention and at follow-up after 12 months. The primary outcome is combined prevalence of selected enteric infections among children under 5 years of age. Secondary outcome measures include soil-transmitted helminth (STH) reinfection in children following baseline deworming and prevalence of reported diarrhoeal disease. We will use exposure assessment, faecal source tracking, and microbial transmission modelling to examine whether and how routes of exposure for diarrhoeagenic pathogens and STHs change following introduction of effective sanitation. Ethics: Study protocols have been reviewed and approved by human subjects review boards at the London School of Hygiene and Tropical Medicine, the Georgia Institute of Technology, the University of North Carolina at Chapel Hill, and the Ministry of Health, Republic of Mozambique. Trial registration number: NCT02362932.